2015
DOI: 10.2149/tmh.2014-34
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Hemorrhagic Fever in a Japanese Traveler with Pre-existing Japanese Encephalitis Virus Antibody

Abstract: An adult Japanese man who had just returned from Thailand developed dengue hemorrhagic fever (DHF). A primary infection of dengue virus (DENV) was confirmed, specifically DENV serotype 2 (DENV-2), on the basis of the detection of the virus genome, a significant increase in the neutralizing antibody and the isolation of DENV-2. DHF is often observed following a secondary infection from another serotype of dengue virus, particularly in children, but this case was a primary infection of DENV. Japan is a non-endem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
0
7
0
2
Order By: Relevance
“…Studies have also shown that JE vaccines have limited effect on the severity of dengue disease [ 35 ]. However, there is limited and inconclusive evidence regarding pre-existing immunity to JEV and subsequent symptomatic or severe presentation of DENV infection [ 12 , 36 ]. In flavivirus infection, the ability to mount an early and vigorous antibody response is associated with better clinical outcomes, indicating that anamnestic, anti-flavivirus immune response induced by prior DENV and JEV infection, for example, is important in conferring protection, or comparatively milder disease outcomes [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that JE vaccines have limited effect on the severity of dengue disease [ 35 ]. However, there is limited and inconclusive evidence regarding pre-existing immunity to JEV and subsequent symptomatic or severe presentation of DENV infection [ 12 , 36 ]. In flavivirus infection, the ability to mount an early and vigorous antibody response is associated with better clinical outcomes, indicating that anamnestic, anti-flavivirus immune response induced by prior DENV and JEV infection, for example, is important in conferring protection, or comparatively milder disease outcomes [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…До 2 % таких жителей на протяжении жизни переболевают японским энцефалитом и имеют нейтрализующие антитела к его возбудителю -вирусу японского энцефалита. Их коли-чество среди людей моложе 50 лет постоянно увеличива-ется из-за осуществления различных программ по вак-цинации населения против японского энцефалита, тем самым увеличивается риск геморрагического течения ли-хорадки Денге при первичном заражении DENV [107]). …”
Section: феномен антителозависимого усиления инфекцииunclassified
“…Исследовате-ли считают, что программы по вакцинации населения против вируса японского энцефалита, в тех районах, где одновременно с ним циркулирует и MVEV, могут способствовать развитию эпидемии энцефалита до-лины Мюррей. В более поздних работах обсуждалась связь с предыдущей вакцинацией против японского энцефалита тяжелого течения лихорадки Денге у жи-телей Японии [107].…”
Section: феномен антителозависимого усиления инфекцииunclassified
“…The mechanism of ADE remains only partially understood. Fcγ receptor (FcγR)-mediated uptake of virionantibody complexes into permissive cells may be one explanation for the enhancement of DENV infection (Sato et al, 2015). FcγR is a multi-subunit complex that is distributed on the surfaces of many types of immune cells, such as dendritic cells, macrophages and mast cells, and recognizes the Fc regions of immunoglobulins.…”
Section: Role Of Antibody-dependent Enhancement (Ade) In Dhf Pathogenmentioning
confidence: 99%